PSYCHOLOGICAL ATTRIBUTES AND DEMOGRAPHIC PROFILE OF UG STUDENTS WITH ICT APPLICATION: A COMPARATIVE STUDY BETWEEN AGRICULTURE UNIVERSITIES OF TANZANIA AND INDIA - R. NEELA RANI, LULU LUFLENGE, A. MARY SWARNA LATHA and (The Journal of Research, PJTSAU, 2019)
This study was designed to assess the psychological attributes and demographic profile of UG students between Sokoine Agriculture University of Tanzania (SUA) and India (PJTSAU) and to find out the significance of difference in psychological attribute and demographic profile of the students of both universities. Exploratory research design was adopted to conduct the study whereby 200 UG students from two colleges participated in the study. Data was analyzed using different statistical techniques which included descriptive statistics, mainly mean and standard deviation and paired sample t-test. It was hypothesized that there will be no significant difference between students of PJTSAU and SUA in psychological attributes and demographic profile of UG students .Overall, the demographic profile of the students of PJTSAU and SUA differed in certain aspects, but showed somewhat uniform trend too. Paired sample t-test revealed a significant difference on demographic profile of UG students of SUA (M= 26.32, SD=2.9) compared to PJTSAU (M= 25.20, SD=2.4); t (99) = 3.24, p < 0.01. In psychological profile the PJTSAU students (M= 8.92, SD=3.6) were above than (M= 6.87, SD=3.1); t (99) = 3.56, p < 0.04 SUA. Hence null hypothesis was rejected and empirical was accepted, as there is significant difference between students of PJTSAU and SUA in psychological attributes and demographic profile.